What’s so Special about Legal Translation? - Harvey, Malcolm (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2002)
AbstractThe aim of this paper is to provide an overview of the main difficulties of legal translation and discuss whether they justify claims that it is a category in its own right. It proposes a wide-ranging definition of legal translation, which calls into question some received notions about its inherent difficulties.